Modelagem da qualidade da água do Rio Poti - Oliveira Filho, Antônio Alves de (2014)
The disorderly growth of the capital of Piauí, marked mainly by housing occupancy on the banks of river Poti and the existence of clandestine connections of raw sewage in rainwater drainage pipes, has contributed significantly to the pollution of the waters of the river basin of the Parnaíba River (semiarid region Brazil). This research consists of making water quality measuring campaigns in Poti river and sewage released that, via gallery rainwater, focusing on a river stretch of 36.8 km long, located in the city of Teresina / PI, as well as mathematical modeling of water quality of the river based on WHAT-UFMG platform. The research is presented as the first study involving modeling of water quality in a water body of the state of Piauí. Modeled components were: dissolved oxygen (DO), biochemical oxygen demand (BOD) and thermotolerant coliform (TC). The results of field measurements indicated TC parameter discontinuities with respect to CONAMA Resolution n° 357/2005. The calibration of the decay coefficients for each parameter resulting in deviations between measured and modeled data of up to 20%, which shows that the QUALUFMG can be used as a basis for predicting the quality of water in rivers located in semiarid regions. The calibrated model was also compared to field data from the literature. Finally, simulations were performed for different flow scenarios (Q10, Q90 and Q7,10), with consistent results and that can be used for the management of water resources in the state of Piauí.